The Development of Education in the Concept of Independent Campus in the Perspective of the Philosophy of Educational Progressivism - Samaloisa, Benhur; Simbolon, Bintang (Sahabat Publikasi, 2025)
Education in Indonesia is a very important and valuable need, so it is considered a significant goal stated in the formal constitution of the Republic of Indonesia, especially in the fourth part of the Preamble to the 1945 Constitution, which explicitly states that providing education to the people is the responsibility of answering the country. The aim of this research is to understand the development of independent campuses from the perspective of the progressivism educational philosophy. This research uses a qualitative approach through literature research. The development of independent campuses substantially reflects the principles of progressivism educational philosophy, because it advocates modernization and democratization to achieve independence and freedom in education. In the context of its educational and learning orientation, the independent campus is in line with the educational philosophy of progressivism, with a focus on developing various skills, scientific disciplines, social sensitivity and personality in students. The learning and education approach championed by the philosophy of progressivism aims to provide as many benefits as possible to students or students through optimizing their attention and talents. The benefits of this learning process are not only for individuals, but also for society as a whole, so that this helps create a just and prosperous life for all. Independent Campus is closely linked to the principles of progressivism because it emphasizes the importance of independence, modernization and democratization in education. This orientation definitely requires support from all parties so that there are no instant negative consequences in Indonesia.